Tree-inception in PMMA with a barrier; Journal of Physics D: Applied Physics; Vol. 37, iss. 16 - Gefle O. S.; Lebedev S. M. Sergey Mikhailovich; Pokholkov Y. P. Yuri Petrovich; Gockenbach E.; Borsi Н. (2004, 2004)
Title screen